Interferon-inducible SAMHD1 restricts viral replication through downregulation of lipid synthesis - An, Ni; Ge, Qinghua; Shao, Huihan; Li, Quanjie; Guo, Fei; Liang, Chen; Li, Xiaoyu; Yi, Dongrong; Yang, Long; Cen, Shan (Frontiers in Immunology, 2022)
Background Type I interferon (IFN) inhibits virus infection through multiple processes. Recent evidence indicates that IFN carries out its antiviral activity through readjusting of the cellular metabolism. The sterile alpha motif and histidine-aspartate domain containing protein 1 (SAMHD1), as an interferon-stimulated gene (ISG), has been reported to inhibit a number of retroviruses and DNA viruses, by depleting dNTPs indispensable for viral DNA replication. Here we report a new antiviral activity of SAMHD1 against RNA viruses including HCV and some other flaviviruses infection. Methods Multiple cellular and molecular biological technologies have been used to detect virus infection, replication and variation of intracellular proteins, including western blotting, qRT-PCR, Gene silencing, immunofluorescence, etc. Besides, microarray gene chip technology was applied to analyze the effects of SAMHD1 overexpression on total expressed genes. Results Our data show that SAMHD1 down-regulates the expression of genes related to lipid bio-metabolic pathway, accompanied with impaired lipid droplets (LDs) formation, two events important for flaviviruses infection. Mechanic study reveals that SAMHD1 mainly targets on HCV RNA replication, resulting in a broad inhibitory effect on the infectivity of flaviviruses. The C-terminal domain of SAMHD1 is showed to determine its antiviral function, which is regulated by the phosphorylation of T592. Restored lipid level by overexpression of SREBP1 or supplement with LDs counteracts with the antiviral activity of SAMHD1, providing evidence supporting the role of SAMHD1-mediated down-regulation of lipid synthesis in its function to inhibit viral infection. Conclusion SAMHD1 plays an important role in IFN-mediated blockade of flaviviruses infection through targeting lipid bio-metabolic pathway.